Effects of structural defects on low-velocity impact damage mechanisms of three-dimensional braided composites based on X-ray micro-computed tomography - Mengyao Sun (Elsevier, 2021)
This paper presents the influence of the braiding structural defects on the low-velocity impact damage mechanisms of three-dimensional (3D) braided carbon/epoxy composites. The braiding structural defects are formed by reducing-yarn process. Also, for the samples with and without reducing-yarn defects, two kinds of braided angles, 20° and 40°, are selected, respectively. All the samples are experimentally tested via drop-weight impact method. X-ray micro-computed tomography (micro-CT) techniques are employed to identify the internal damage characteristics. The results show that the structural defects significantly influence the impact mechanical properties of 3D braided composites. Compared to non-defect samples, 3D braided composites with reducing-yarn defects exhibit lower loads and less response time. Moreover, the 40° samples exhibit lighter damage and less damage volume than that of the 20° samples.